Performance Evaluation of Hot Pepper Cultivars for Green Fruit Production under Open Field Conditions in Kathmandu Valley, Nepal - Shrestha, Surendra Lal (Genetics, Plant Breeding and Seed Science, 2025)
An evaluation trial was conducted at Khumaltar during the second week of April in 2021 and 2022 to assess the performance of nine hot pepper (Capsicum spp.) cultivars received from the National Gene Bank, with ‘Pusa Jwala’ as the local check. The trial followed a randomized complete block design with three replications and a spacing of 60 × 60 cm. The crop was fertilized with 150:120:100 kg/ha of nitrogen, phosphorus, and potassium, respectively, along with 20 tons/ha of farmyard manure. The objective was to identify high-yielding cultivars with tolerance to insect pests and diseases, as well as traits preferred by consumers and farmers under open field conditions in the central mid-hills of Nepal. Observations were recorded on vegetative growth, pest and disease incidence, yield components, morphological traits, and end-user preferences. Among the tested cultivars, CO5066-2 showed superior performance in terms of uniform and vigorous growth, early fruiting (54 days), minimal insect damage (1.6 on a 1–5 scale), low leaf spot incidence (1.75), highest yield (13.68 t/ha; 525 g/plant), and strong acceptance by consumers (4.9) and farmers (4.0). CO5061 also performed well, with vigorous growth (4.0), moderate time to flowering (49.3 days) and fruit set (55.5 days), low insect damage (1.85), moderate leaf spot resistance (2.15), higher fruit set per node (1.05), and yield of 11.39 t/ha (410 g/plant). It also received favorable ratings from consumers (3.5) and farmers (3.7). Both CO5066-2 and CO5061 outperformed the check variety ‘Pusa Jwala’ in terms of yield, pest and disease resistance, and user preference. These cultivars are recommended for further on-farm validation in the central mid-hills of Bagmati Province.